Avaliação Dos Impactos Dos Investimentos Nas Plantações Florestais Da Portucel-Moçambique Nas Tecnologias Agrícolas Das Populações Locais Nos Distritos De Ile E Namarrói, Província Da Zambézia - Sitoe, Almeida (Observatório do Meio Rural, 2017)
O presente estudo é parte integrante do projecto “Efeitos dos grandes projectos sobre o meio rural e a agricultura (Portucel- Moçambique)” realizado pelo Observatório do Meio Rural (OMR). Especificamente, as questões que o presente estudo procura responder são: (i) quais as mudanças que ocorreram em termos de acesso a tecnologias de produção agrícola nos distritos de Ile e Namarrói desde que a Portucel iniciou as suas actividades; e (ii) que impactos houve nos sistemas de produção agrícola em termos de produtividade e rendimento. Para responder às questões colocadas neste estudo, foi realizada uma visita de reconhecimento aos dois distritos, encontros com quadros de direcção e operários da empresa Portucel Moçambique, encontros com os provedores de serviços à Portucel Moçambique, as instituições do Estado e as Comunidades abrangidas pelos projectos de plantações florestais nos distritos de Ile e Namarroi, Província da Zambézia.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; agriculture / agricultura; rural development / desenvolvimento rural; ⛔ No DOI found

The political economy of corridors, commercialisation and agrarian change in eastern Africa - Scoones, Ian; Smalley, Rebecca (2017)
The political economy of agricultural growth corridors: some first thoughts: • Neither state-driven ‘high modernism’ (Scott) nor enclave capitalism (Ferguson), but context-specific hybrid dynamic. • Endogenous capital and dynamics of accumulation crucial: diverting, upsetting , recasting grand plans and investments. • Contested visions of ‘development’ and ‘progress’ being played out, challenging and reconfiguring authority, with tensions and contradictions among elite alliances. • The everyday politics of corridors: contentious local politics (and resistances) intersect with wider corridor politics, influencing outcomes. • Who wins and who loses depends on terms of incorporation, predicated on both contemporary politics, but also long-run historical antecedents
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Policy analysis Food security, nutrition, climate change resilience, gender and the small-scale farmers Mozambique - Care; ActionAid (ActionAid and Care, 2017)
The analysis covers both national specific policies and those policies and commitments that the Government of Mozambique has signed as part of global collective efforts. The analysis aims to become a baseline to better understand the policy gaps and implementation challenges in in FNS and CCR towards women and smallholders in Mozambique. The main purpose of this analysis is to become useful source and instrument in the implementation of CARE Mozambique Advocacy Strategy, and also for the Government of Mozambique, donors and civil society organizations, to better identify the challenges for a more effective investment in gender transformative, climate resilient and nutrition smart agriculture.
Keywords: *snowball; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; climate change / mudanças climáticas

O agronegócio no desenvolvimento do meio rural em Moçambique: perceção e análise das cadeias de valor de milho e da mandioca na província de Nampula - Linha, Paulo (Universidade de Lisboa, 2017)
O Agronegócio em Moçambique poderá ser um factor dinamizador da agricultura, chave para o desevolvimento económico, elemento para a equidade no desenvolvimento social e fundamental para a redução da pobreza e da fome. O estudo analisa as perceções dos atores do agronegócio do milho e da mandioca sobre o impacto destas culturas na vida económica e social no meio rural. Diante desta perspetiva, esta pesquisa teve como objetivo investigar prospectivamente as cadeias de valor das culturas do milho e da mandioca, no corredor de Nacala, com vista a identificar formas de potenciar o desenvolvimento do agronegócio como fator dinamizador da promoção do desenvolvimento socioeconómico sustentável no meio rural. Os resultados alcançados indicam que em Moçambique, de forma geral, o agronegócio do milho e da mandioca é potencial pilar dinamizador que poderá contribuir para o desenvolvimento da agricultura e impulsionar o crescimento económico e o desenvolvimento social se o Estado colocar-se na dianteira na criação, nas zonas de produção, de infraestruturas públicas para a prática de uma agricultura economicamente sustentável e uma legislação flexível e promotora de um clima propício para o agronegócio. Com as infraestruturas públicas criadas nos centros de produção deve-se optar, pelo envolvimento de todos atores do agronegócio num sistema de Integração e Coordenação Vertical, apostando na transformação da baixa renda da agricultura rural em agricultura comercial e competitiva para que efetivamente o agronegócio seja um dos pilares para o combate da fome e da pobreza no meio rural. A Integração e Coordenação Vertical, significa a existência de instituições âncoras que se dedicam a puxar a atividade do agronegócio dos produtores locais na base contratual. Esta forma promete rápida integração ao mercado, crescimento económico, inovação tecnológica, ao mesmo tempo em que protege os direitos e a autonomia do produtor sob regime de integração e coordenação. Agribusiness in Mozambique could be a driving force for agriculture, key to economic development, an element for equity in social development and fundamental to reducing poverty and hunger. The study analyzes the perceptions of corn and cassava agribusiness actors on the impact of these crops on economic and social life in rural areas. The objective of this research was to investigate prospectively the corn and cassava value chains in the Nacala corridor in order to identify ways to promote the development of agribusiness as a driving force for the promotion of sustainable socioeconomic development in the environment rural. The results indicate that, in general, corn and cassava agribusiness in Mozambique are potential pivotal factors that could contribute to the development of agriculture and boost economic growth and social development, if the government takes the initiative to build public infrastructures for an economic sustainable agriculture as well as create a flexible legislation that promotes a proper environment for agribusiness. With the public infrastructures created in the production centers, one must opt for the involvement of all agribusiness actors in a system of Integration and Vertical Coordination, betting on the transformation of low income from rural agriculture into commercial and competitive agriculture so that agribusiness is effectively a pillar to combat hunger and poverty in rural areas. Integration and Vertical Coordination means the existence of anchor institution dedicated to pull the agribusiness activity of the local producers in the contractual basis. This form promises rapid market integration, economic growth, technological innovation, while protecting the rights and autonomy of the producer under integration and coordination.
Accepted: 2018-04-09T13:15:08Z
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; agriculture / agricultura; private sector / setor privado

Mozambique: A Political Economy Analysis - Orre, Aslak; Rønning, Helge (Chr. Michelsen Institute, 2017)
This report uses a political economy analysis to shed light on some of the paradoxes that characterise Mozambique mid 2017: Entrenched poverty, the resuscitated armed conflict/war, the trust crisis between the Mozambican (Frelimo) government and its development partners, the spiralling debt and the party-state.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; conflict / conflito; poverty / pobreza